Characteristics of Terrestrial Heat Flow and Lithospheric Thermal Structure in Typical Intermountain Basin at the Eastern Foot of Yanshan Mountain, North China - Liu, Feng; Wang, Andong; Wang, Guiling; Zhang, Wei; Liao, Yuzhong; Tong, Jue (Frontiers in Earth Science, 2021)
The Yanshan area is rich in geothermal resources. However, very limited research has been done on the geothermal resources of intermountain basins in the area, which restricts the exploration and development of geothermal resources. In this study, the Yanheying Basin, a typical intermountain basin located in the eastern foothills of Yanshan Mountain, is selected to perform a comprehensive analysis in respect of heat flow and lithospheric thermal structure, to have a better understanding of the geothermal background and resource utilization potential of the area. The methods of deep borehole temperature logging, and rock sampling and testing were applied. Together with geological and geophysical data collected in the surrounding basins, the thermophysical parameters of rock formations, terrestrial heat flow and temperature distribution on a crustal-scale around the basin were analyzed . Results show that the ratio of crust heat flow to that of the mantle in the Yanheying Basin is 0.68 which falls in the range of that of the North China Plain (0.6-0.8), showing an obvious result of lithospheric thinning. The results also show that both crust and mantle heat flows in the Yanheying Basin and even in the entire Yanshan area are far lower than those of the North China Plain, indicating that the crust of the area has experienced a low degree of damage. This provides a piece of good thermodynamic evidence for the spatial variation of North China Craton destruction. The depth of the Curie surface in the study area is estimated to be about 24 km, which is consistent with the result of aeromagnetic data analysis and confirms the results of lithospheric thermal structure and deep temperature distribution in the Yanheying Basin. The Yanheying Basin has certain potential for geothermal resources utilization in the depth of 2-6 km, where may exist several carbonate thermal reservoirs with medium-temperature geothermal water. The above results can provide new insights into the geothermal research and exploration of intermountain basins in the Yanshan area.